Tissue culture and biological activities of Gardenia jasminoides Ellis / Reza Farzinebrahimi - Farzinebrahimi, Reza (2012)
In order to establish an efficient in vitro propagation protocol for Gardenia jasminoides Ellis, Murashige and Skoog (MS) and woody plant medium (WPM) with different concentrations and types of auxin and cytokinin were used. The leaf explants of G. jasminoides were cultured on MS and WPM medium containing 3% sucrose and different concentrations of NAA, IBA, IAA, 2,4-D as aux-in and TDZ & Kn as cytokinin with range of 0-5 mg l-1 in order to obtain callus, shoot and root formation. After 2 weeks, the callus was formed on both types of media sup-plemented with various hormones at different concentrations. The results showed that 100% callus was formed on MS and WPM supplemented with 2, 2.5 and 3 mg l-1 of NAA. No significant difference in callus formation was observed between various auxins on WPM media, in contrast, MS media showed significant differences between IAA to other auxins. In addition, Kinetin and TDZ supplemented to MS media showed statistical differences compare to WPM media. When leaf explants were cultured on MS and WPM media supplemented with a combination of all used auxins with TDZ and Kn, no shoot formation was observed. Rooting started on both media supplemented with various auxins after the fifth weeks. MS medium supplemented with (1.5 and 2 mg l-1) NAA showed higher response for root length (14.8 and 13.4 cm) and IAA (4.5 and 5 mg l-1) supplemented to WPM media showed the longest root length (18.3 and 18.7 cm), respectively. Data analyses showed significant differences in WPM medium supplemented with IAA, NAA and IBA, respectively. However, MS media showed statistical differences when supple-mented with NAA compare to IAA and IBA. Fresh grown callus on MS medium supplemented with NAA (3 mg l-1) and Kn (5 mg l-1) were 34.23 g and 3.39 g respectively. In addition, 30.04 g and 3.78 g were the fresh weight of the callus, cultured on WPM media supplemented with (2.5 mg l-1) NAA and (4 mg l-1) Kn. A high amount of callus was formed from leaf explants of G. jasminoides Ellis on both MS and WPM media supplemented with different concen-trations of NAA and IBA. Extracts from callus grown on both MS and WPM supplemented with NAA showed antibacterial activity against Escherichia coli (gram-negative) and Bacillus cereus (gram-positive). The other extracts from in vivo and in vitro calluses showed no antibacterial zone against the rest of the bacteria tested. The in vitro-grown callus derived using NAA, IBA, TDZ, and Kn disclosed the antioxidant activity of the callus extract which is significantly different from the intact plant.